Opcje realne i możliwości ich aplikacji we współczesnych przedsiębiorstwach - Sus-Januchowska, Aleksandra (The Real Options Analysis and Its Role in Recent Organizations, 2008)
The article concentrates on real options analysis and its role in recent organizations. This approach is relatively new in strategic management and a small amount of companies are applying this method. In the article the real options analysis is presented as a way of thinking, analytic tool and an organizational process.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 365-371